Adding value to cereals, roots and tubers (1) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Adding value to cereals, roots and tubers. Developments and opportunities in small-scale enterprise development in Africa.